LEBANON’S NATIONAL IDENTITY: WALKING BETWEEN RAINDROPS? - Stewart, Hannah (The Levantine Review, 2012)
As the Levant continues to roil in upheaval in this second decade of the twenty-first century, Lebanon, a state notorious for its history of communal dissensions, remains remarkably stable, advancing a splendid model–albeit an uneasy model–of inter-communal coexistence. Lebanon’s history as a refuge for persecuted minorities and an entrepôt of international trade, in some ways, fostered a unique culture of openness and tolerance making it an “oddity” in its neighbourhood, and contributing to the formation of what can be termed a “distinct Lebanese identity.” A glance at Lebanon’s languages, traditions, history, and culture of power-sharing, suggests that despite periods of violence, patterns of coexistence among Lebanon’s various groups have developed organically, and often logically, since the French Mandate period, and can perhaps offer a model for emulation in a Levant of fractious ethnic mosaics.